2019
DOI: 10.7150/jca.30463
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of site-specific metastases in lung cancer: A population based study

Abstract: Background : Studies on prognosis of different metastasis sites in patients with lung cancer are limited. The aim of present study was to investigate the prognostic value of metastases sites among patients with metastatic lung cancer. Methods : Between 2010 and 2014, patients diagnosed with metastatic lung cancer were selected using the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier methods were adopted and multivariable Cox regression models were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 37 publications
5
63
1
Order By: Relevance
“…Moreover, the proportion of patients with brain metastases (36%) and liver metastases (27%) were high in our study. SCLC patients with brain metastases and/or liver metastases have a worse prognosis, 26 although there were no statistical differences in PFS and OS between patients with and without brain metastases, or between patients with and without liver metastases in our study (Table 3). The median OS is 4 to 5 months for patients with recurrent or chemorefractory SCLC 27 .…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, the proportion of patients with brain metastases (36%) and liver metastases (27%) were high in our study. SCLC patients with brain metastases and/or liver metastases have a worse prognosis, 26 although there were no statistical differences in PFS and OS between patients with and without brain metastases, or between patients with and without liver metastases in our study (Table 3). The median OS is 4 to 5 months for patients with recurrent or chemorefractory SCLC 27 .…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies showed that the numbers of distant metastases were significantly correlated with outcomes in some types of cancer 25 , 26 , but a similar correlation was not seen in pancreatic cancer. Oweira et al found no significant difference in OS between pancreatic cancer patients with single metastasis and multiple metastases (P=0.409) 10 .…”
Section: Discussionmentioning
confidence: 83%
“…Despite the decline in the rate of non-small cell lung cancer (NSCLC) in recent years, it remains the leading cause of cancer mortality worldwide, 1.8 million people are diagnosed with lung cancer, and 1.6 million individuals died as a result of the disease in 2017 worldwide (1). Accurate diagnosis and precise prognostic predictions are critical for targeted treatment and prolonging the overall survival of patients with NSCLC (2). However, commonly used biomarkers, such as carcino-embryonic antigen and Cyfra21-1, offer low sensitivity and specificity and are not appropriate for clinical applications (3,4).…”
Section: Introductionmentioning
confidence: 99%